Relevansi Prinsip Welfare State terhadap Perlindungan Hukum Kreditur dan Debitur Kredit Macet Akibat Force Majeur Gempa Palu 2018 - Jihan Dalilah Ismah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Force majeure, such as the 2018 Palu earthquake, triggers non-performing loans due to the loss of livelihoods, although payment obligations are not automatically extinguished. This research employs a socio-legal method with statutory and conceptual approaches, analyzed through the principle of the welfare state. The results indicate that the credit restructuring policy issued by the Financial Services Authority (OJK) provides legal protection that balances the interests of both creditors and debtors, while simultaneously reflecting the implementation of the welfare state principle in maintaining justice and legal certainty.